Analisis penerapan teknologi pertanian di Desa Sroyo: studi kasus pada petani padi dan sayuran - Alya Nur Aida, Farah; Fitriawan, Hafidz Rizki; Wahab, M. Ghozali Abdul; Wardhani, Olivia Putri; Aanjani, Salsabila Railla Putri; Antriyandarti, Ernoiz (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: The application of agricultural technology has an important role in increasing the productivity and efficiency of farming businesses. A case study in Sroyo Village, Jaten District, Karanganyar Regency shows that the application of technological innovations such as tractor engines, rice harvesting machines and rice milling units has had a positive impact on increasing agricultural yields. Apart from that, the transfer of knowledge and knowledge through extension by the Agricultural Extension Center (BPP) also contributes to improving farmers' skills in crop cultivation and animal husbandry. Methods: The analytical method used is the descriptive method. Findings: Although there are challenges such as environmental pollution due to industrial waste around agricultural land, this problem can be overcome by utilizing irrigation from local wells. The main potential of Sroyo Village lies in the rice commodity, where farmers are able to carry out three harvests a year, supported by the availability of adequate irrigation. Conclusion: The application of agricultural technology and knowledge transfer is expected to increase productivity, efficiency and quality of agricultural products, as well as support sustainable agricultural development in the region.